Recent Advance in Disease Modifying Therapies for Spinal Muscular Atrophy - Li-Kai Tsai; Chen-Hung Ting; Yo-Tsen Liu; Cheng-Tsung Hsiao; Wen-Chin Weng; Society for Neurological Rare Disorders-Taiwan (Acta Neurologica Taiwanica)
Spinal muscular atrophy (SMA) is an autosomal recessive motor neuron disease characterized by progressive weakness and atrophy of skeletal muscles. With homozygous survival motor neuron 1 (SMN1) gene mutation, all SMA patients have at least one copy of the SMN2 gene, which provides an opportunity for drug targeting to enhance SMN expression. Current three disease modifying drugs, including nusinersen, onasemnogene abeparvovec, and risdiplam, have demonstrated impressive effectiveness in SMA treatment. Nusinersen is an antisense oligonucleotide targeting SMN2 pre-messenger RNA (mRNA) to modify alternative splicing and is effective in SMA children and adults, administrating via intermittent intrathecal injection. Onasemnogene abeparvovec is an adeno-associated viral vector carrying human SMN1 gene, featuring intravenous injection once in a lifetime for SMA patients less than 2 years of the age. Risdiplam is a small molecule also targeting SMN2 pre-mRNA and is effective in SMA children and adults with administration via oral intake once per day. Patients with SMA should receive these disease modifying therapies as soon as possible to not only stabilize disease progression, but potentially obtain neurological improvement. The development in these therapies has benefited patients with SMA and will potentially provide insight in future drug discovery for other neurodegenerative diseases.